2019
DOI: 10.1182/blood-2019-121694
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Ixazomib, Daratumumab and Low Dose Dexamethasone (Ixa Dara dex) in Unfit and Frail Newly Diagnosed Multiple Myeloma (NDMM) Patients; Results of the Interim Efficacy Analysis of the Phase II HOVON 143 Study

Abstract: Introduction Elderly non-transplant eligible newly diagnosed multiple myeloma (nte-NDMM) patients also benefit from novel therapies, however, overall survival (OS) is inferior in unfit and frail compared to fit patients as defined by the International Myeloma Working Group (IMWG) frailty index. This is caused by a high discontinuation rate due to toxicity. Therefore, a less toxic effective treatment for unfit and frail patients is needed. In view of the favorable safety profile of ixazomib (Ixa)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Daratumumab was also studied in association with ixazomib and low dose dexamethasone in phase II HOVON-143 trial ( 29 ) for unfit and frail patients according to the International Myeloma Working Group Frailty Index (IMWG-FI). Treatment consisted of nine cycles with ixazomib (4 mg on days 1, 8, 15), daratumumab (16 mg/kg weekly cycles 1 and 2; every two weeks cycles 3–6; day 1 cycles 7–9), dexamethasone (in combinations with daratumumab 10 mg).…”
Section: Transplant-ineligible Newly Diagnosed Multiple Myeloma Patiementioning
confidence: 99%
“…Daratumumab was also studied in association with ixazomib and low dose dexamethasone in phase II HOVON-143 trial ( 29 ) for unfit and frail patients according to the International Myeloma Working Group Frailty Index (IMWG-FI). Treatment consisted of nine cycles with ixazomib (4 mg on days 1, 8, 15), daratumumab (16 mg/kg weekly cycles 1 and 2; every two weeks cycles 3–6; day 1 cycles 7–9), dexamethasone (in combinations with daratumumab 10 mg).…”
Section: Transplant-ineligible Newly Diagnosed Multiple Myeloma Patiementioning
confidence: 99%
“…Preliminary data showed an overall response rate (ORR) of 74% and 78% in intermediate and frail patients and a median PFS of 23 and 12 months, respectively. Preliminary analysis showed that discontinuation rates and toxic deaths were low in intermediate-fit patients, but reached 7% and 9% in frail patients, suggesting that this latter group might benefit from even gentler approaches [59].…”
Section: Treatment Considerations For Intermediate-fit and Frail Patimentioning
confidence: 99%
“…Remarkably, new phase II trials are exploring frailty-tailored approaches including mAbs in less toxic combinations in NDMM patients. For instance, the HOVON group is evaluating the combination of daratumumab, ixazomib, and low-dose dexamethasone in intermediate-fit and frail patients [ 28 ]. The IFM2017_03 study will evaluate subcutaneous daratumumab plus lenalidomide vs. standard Rd in frail patients as a dexamethasone-sparing strategy, since steroids are scarcely tolerated in the long term, particularly in elderly populations (NCT03993912).…”
Section: How To Choose Therapy In Nte Ndmm Patientsmentioning
confidence: 99%
“…Many other treatment combinations, based on various mAbs, are currently under investigation. Among them, the HOVON 143 phase II trial enrolled intermediate-fit and frail NDMM patients to evaluate the efficacy and safety of a first-line treatment with the association of daratumumab, ixazomib, and low-dose dexamethasone [ 28 ]. The treatment schedule included an induction phase followed by maintenance therapy.…”
Section: Clinical Trials Evaluating Mab-based Treatments In Nte MMmentioning
confidence: 99%